MRI assessment of suppression of structural damage in patients with rheumatoid arthritis receiving rituximab: results from the randomised, placebo-controlled, double-blind RA-SCORE study - Peterfy, Charles; Emery, Paul; Tak, Paul P; Østergaard, Mikkel; DiCarlo, Julie; Otsa, Kati; Navarro Sarabia, Federico; Pavelka, Karel; Bagnard, Marie-Agnes; Gylvin, Lykke Hinsch; Bernasconi, Corrado; Gabriele, Annarita (Annals of the rheumatic diseases, 2016)
OBJECTIVE: To evaluate changes in structural damage and joint inflammation assessed by MRI following rituximab treatment in a Phase 3 study of patients with active rheumatoid arthritis (RA) despite methotrexate (MTX) who were naive to biological therapy. METHODS: Patients were randomised to receive two infusions of placebo (n=63), rituximab 500 mg (n=62), or rituximab 1000 mg (n=60) intravenously on days 1 and 15. MRI scans and radiographs of the most inflamed hand and wrist were acquired at baseline, weeks 12 (MRI only), 24 and 52. The primary end point was the change in MRI erosion score from baseline at week 24. RESULTS: Patients treated with rituximab demonstrated significantly less progression in the mean MRI erosion score compared with those treated with placebo at weeks 24 (0.47, 0.18 and 1.60, respectively, p=0.003 and p=0.001 for the two rituximab doses vs placebo) and 52 (-0.30, 0.11 and 3.02, respectively; p<0.001 and p<0.001). Cartilage loss at 52 weeks was significantly reduced in the rituximab group compared with the placebo group. Other secondary end points of synovitis and osteitis improved significantly with rituximab compared with placebo as early as 12 weeks and improved further at weeks 24 and 52. CONCLUSIONS: This study demonstrated that rituximab significantly reduced erosion and cartilage loss at week 24 and week 52 in MTX-inadequate responder patients with active RA, suggesting that MRI is a valuable tool for assessing inflammatory and structural damage in patients with established RA receiving rituximab. TRIAL REGISTRATION NUMBER: NCT00578305.
Keywords: dvojitá slepá metoda; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; stupeň závažnosti nemoci; Disease Progression; Double-Blind Method; progrese nemoci; výsledek terapie; Middle Aged; mužské pohlaví; Adult; magnetická rezonanční tomografie; kloubní chrupavka; Magnetic Resonance Imaging; Rituximab; ženské pohlaví; Humans; antirevmatika; Arthritis, Rheumatoid; rituximab; lidé středního věku; revmatoidní artritida; Antirheumatic Agents; dospělí; Female; Severity of Illness Index; Treatment Outcome; Cartilage, Articular; lidé; Male